An introduction to health services research - Walker, Dawn-Marie (SAGE Publications, 2014)
This is a primary, comprehensive textbook for people who are considering undertaking a piece of health-related research. It is an accessible companion with the aim of getting the reader to think broadly about all of the issues that need to be considered when embarking on a project. This is a pragmatic book, a step-by-step guide to research which mirrors the structure of a research project, taking you through the thought process for designing and conducting your study from formulating the right research question at idea inception, ascertaining what methodologies and analysis can answer what type of questions, right through to dissemination, all presented in an easy, digestible style. The book is full of case study illustrations and practical tips such as how to work out a research budget and obtaining funding for your project, discussion of what permissions need to obtained when conducting research with people, and how to involve public and patients. The authors are all experienced researchers and so this book is an accumulation of collective wisdom on common research challenges and issues.--Provided by publisher.